2013
DOI: 10.1111/rda.12235
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Liver Damage Delays Meiotic Resumption in Bovine Oocytes through Impairment of Signalling Cascades Originated from Low p38MAPK Activity in Cumulus Cells

Abstract: The main objective of the present study is to investigate the molecular mechanism underlying the delay in progression of nuclear maturation in oocytes derived from cows with damaged livers (DL cows), which was previously reported. In present study, delayed progression of nuclear maturation of oocytes derived from DL cows relative to oocytes derived from cows with healthy livers (HL cows) was accompanied by low maturation promoting factor (MPF) activity (0.43 fold, p < 0.05). When cumulus cells were removed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…COCs were culture in medium containing 0 or 10 µM of MG132 and after maturation periods oocytes were denuded from the granulosa cells and subjected to western blot analysis. To quantify ubiquitinated protein, 40 oocytes were lysed in 20 µL of Laemmli sample buffer (Bio-Rad Laboratories Inc., Hercules, CA, USA) and analyzed by western blot, using a method described previously [25] with slight modifications. Briefly, rabbit polyclonal ubiquitin primary antibody (1∶1000; #3933; Cell Signaling Technology) was diluted using immunoreaction enhancer solution 1 (Toyobo, Osaka Japan), And donkey anti-rabbit IgG HRP-linked secondary antibody (1∶20 000; Abcam, Tokyo, Japan) was diluted in immunoreaction enhancer solution 2.…”
Section: Methodsmentioning
confidence: 99%
“…COCs were culture in medium containing 0 or 10 µM of MG132 and after maturation periods oocytes were denuded from the granulosa cells and subjected to western blot analysis. To quantify ubiquitinated protein, 40 oocytes were lysed in 20 µL of Laemmli sample buffer (Bio-Rad Laboratories Inc., Hercules, CA, USA) and analyzed by western blot, using a method described previously [25] with slight modifications. Briefly, rabbit polyclonal ubiquitin primary antibody (1∶1000; #3933; Cell Signaling Technology) was diluted using immunoreaction enhancer solution 1 (Toyobo, Osaka Japan), And donkey anti-rabbit IgG HRP-linked secondary antibody (1∶20 000; Abcam, Tokyo, Japan) was diluted in immunoreaction enhancer solution 2.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Tanaka et al . [ 47 ] showed that delayed meiotic maturation of oocytes in dairy cows with damaged livers is induced by slow gap junctional communication closure between oocytes and cumulus cells, which results in lower fertility. Furthermore, cows with damaged livers exhibit lower concentrations of growth factors in their follicular fluid, compared with those of cows with healthy livers [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…CG distribution is a marker of oocyte cytoplasmic maturation, and the distribution pattern is reportedly regulated by microfilaments whose polymerization depends on ATP [ 28 , 32 , 33 ]; this suggests that low ATP content during oocyte maturation prevents proper CG migration. In addition, we previously showed that the timing of GV breakdown was delayed in oocytes derived from DL cows, whereas the final maturation rates were similar in oocytes from HL and DL cows [ 7 , 8 ]. Thus, the short duration of nuclear maturation may limit the proper distribution of CGs.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of liver conditions and donor cow selection were conducted as described in our previous report [ 7 , 8 ]. Briefly, the liver conditions were visually diagnosed based on the surface and sectional appearance by onsite veterinarians at the slaughterhouse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation